PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH PADA PT. BANK TABUNGAN NEGARA MEDAN - Rahmawanty, Annisa (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
This research aims to study and analyze the effect of service quality and trust on customer loyalty at PT. Bank Tabugan Negara Medan. Research methodology used is descriptive method of analysis and multiple linier. Data processing were performed using SPSS (Statistical product service solution) 19.00 for windows. Result showed that significant effect of service quality on customer loyalty PT.Bank Tabungan Negara Medan. Value sig 0,000 < 0,05. Confidence significant effect on customer loyalty PT.Bank Tabungan Negara Medan. Value sig 0,000 < 0,05